Oral health needs of athletes with intellectual disability in Southern Europe: Greece, Italy and Spain. (9th January 2021) - Fernández Rojas, Carla; Emmanouil, Dimitris; Dellavia, Claudia; Limeres, Jacobo; Castro, Natalia; Marks, Luc A.M.
Abstract: Aims: The population with intellectual disabilities (ID) has been reported to be a vulnerable population in terms of oral health. The aims of this study were to evaluate the oral condition and treatment needs of Special Olympics (SO) athletes from Greece, Italy and Spain. Methods and results: A cross‐sectional study was performed with data collected in annual SO events held in Greece, Italy and Spain, between 2010 and 2012. The recorded parameters were the presence/absence of edentulism, untreated decay, filled or missing teeth, sealants, tooth injury and signs of gingival disease. Among the main findings, the prevalence of untreated decay was 57.0% in Greece, 48.8% in Italy and 41.7% of the Spanish athletes. The prevalence of signs of gingival disease was 61.1% in Greece, 60.6% in Italy and 66.1% in Spain. While the majority of the athletes were in need of dental treatment. Conclusions: Oral disease is an unresolved problem among athletes with ID in these Mediterranean countries. Therefore efforts should be directed to meet their treatment needs and to prevent oral disease.